Matching Method for Power Grid Fault Handling Plan Based on Semantic Enhancement - Fei MENG; Jiangpeng LI; Tao LI; Jianzhong XU; Haiyang GAO; Yongtian QIAO (Zhongguo dianli)
In order to improve the matching efficiency and accuracy of grid fault handling plan, a semantic enhancement-based grid fault handling plan matching method is proposed. Firstly, the multi-dispatch objects entities in the fault handling plan are characterized as computable word vectors by fine-tuning the hyperparameters of the bidirectional encoder representations from transformers (BERT) model, and integrated into the conditional random field (CRF) model to identify the dispatch objects entity categories. And then, the semantic distance between the grid fault information and dispatch objects are computed based on the residual vector-embedding vector-encoded vector (RE2), and a grid fault handling plan matching model is established based on BERT-CRF-RE2. Finally, through validation of the data of a regional power grid, the proposed model effectively solves the problem of low plan matching accuracy rate.